PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN TRANSPARANSI PUBLIK TERHADAP AKUNTABILITAS KEUANGAN DI BKAD KABUPATEN GORONTALO - Palowa, Anisa Rahmatia H.; D. Lantowa, Felmi; Yusuf, Fitria Melynsyah (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the effect of the implementation of the Regional Financial Accounting System (SAKD) and public transparency on financial accountability at the Regional Finance and Asset Agency (BKAD) of Gorontalo Regency. The research method used is a descriptive quantitative approach with a purposive sampling technique, involving 33 respondents from BKAD employees. Data collection was carried out through a closed questionnaire and analyzed using multiple linear regression with the help of SPSS version 25. The results of the study indicate that both the implementation of SAKD and public transparency partially and simultaneously have a positive and significant effect on financial accountability. Public transparency has a dominant influence with a regression coefficient of 0.542 compared to the implementation of SAKD of 0.416. The Adjusted R² value of 0.913 indicates that both variables are able to explain 91.3% of the variation in financial accountability. The conclusion of this study shows that strengthening the accrual-based accounting system and increasing public information disclosure are strategic steps in realizing transparent and accountable regional financial governance. Keywords: Regional Financial Accounting System, Public Transparency, Financial Accountability